1974
DOI: 10.1113/jphysiol.1974.sp010478
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the physiological effects of monocular deprivation in kittens: further evidence for a sensitive period

Abstract: 2. Kittens were monocularly deprived until various ages, from 5 to 14 weeks, at which time reverse suturing was performed: the initially deprived right eye was opened and the left eye closed for a further 9 weeks before recording from the visual cortex.3. Reverse suturing at 5 weeks caused a complete switch in ocular dominance: every cell was dominated by the initially deprived right eye. Reverse suturing at 14 weeks, however, had almost no further effect on ocular dominance: most cells were still driven solel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
216
1
2

Year Published

1984
1984
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(231 citation statements)
references
References 25 publications
11
216
1
2
Order By: Relevance
“…These findings establish 7 d of early MD in mice as a useful protocol to investigate strategies for reversing ocular dominance plasticity and promoting recovery from amblyopia. It has been known for many years from work in kittens and monkeys that deprivation-induced synaptic depression can be reversed if normal vision is restored in the weak (amblyopic) eye and the fellow eye is occluded (11,12). However, gains in the amblyopic eye often come at the expense of vision in the fellow eye, may be temporary, and are rarely accompanied by improvement in binocularity (9,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings establish 7 d of early MD in mice as a useful protocol to investigate strategies for reversing ocular dominance plasticity and promoting recovery from amblyopia. It has been known for many years from work in kittens and monkeys that deprivation-induced synaptic depression can be reversed if normal vision is restored in the weak (amblyopic) eye and the fellow eye is occluded (11,12). However, gains in the amblyopic eye often come at the expense of vision in the fellow eye, may be temporary, and are rarely accompanied by improvement in binocularity (9,(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…This "reverse occlusion" approach has been validated in animals (11,12) and represents the cornerstone of current treatment (patching therapy) of human amblyopia (13)(14)(15)(16). However, this treatment has well-known limitations that include poor compliance, potential loss of vision through the newly patched eye, failure to recover binocular vision, and a declining treatment efficacy with age (15,(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…The extent to which the initial effects of deprivation can be reversed and the speed of the changes depend upon the age at which reverse occlusion begins (Blakemore & Van Sluyters 1974;Movshon 1976a;Blakemore et al 1978Blakemore et al , 1981. Indeed, it has been argued that the temporal profile of the declining ability to reverse prior deprivation-induced effects represents a separate critical period for recovery (Daw 1998(Daw , 2002(Daw , 2003Lewis & Maurer 2005).…”
Section: Key Findings and Concepts Derived From Early Animal Studies mentioning
confidence: 99%
“…Indeed, studies in animals have shown that monocular deprivation (MD) impairs visual cortical responses to the deprived eye and affects axonal morphology and dendritic spine density only if performed during a critical period of postnatal development (2)(3)(4)(5)(6). The ability to recover from the deficits induced by MD declines with age; reopening the previously deprived eye or reverse lidsuturing (RS) in young animals results in full recovery of ocular dominance, but these procedures become progressively less effective with age and are practically ineffective in the adult (7)(8)(9). Recovery from the amblyopic effect of MD is also progressively less efficient during development.…”
mentioning
confidence: 99%